Pela dan Perjamuan Kudus dalam Lensa Teologi Sakramental Susan Ross - Michael Bryan; Hendra Gunawan Simatupang (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. This article discussed the differences of pela as a Moluccan cultural rite and Holly Supper as a Christian rites in the reality of Islam-Christian reconciliation in Maluku based on sacramental theology view of Susan Ross. In Maluku, both Islam and Christian community attack each other due to the distrust that arise from a conflict that happened in 1999. Both Holly Supper, as a Christian rite, and pela, as a Moluccan sacred cultural rite, offeres the uniqueness of the reconciliation process. Using Susan Ross’ perspective on sacramental theology, pela and the Holly Supper could be developed to a new sacred rite that embraces both Christian and Islam community to maintain the reconciliation in Maluku without eliminating the theological perspective on how God works in Moluccan society.Abstrak. Artikel ini mendiskusikan perbedaan pela sebagai ritus budaya Maluku dan Perjamuan Kudus sebagai ritus Kristen dalam rekonsiliasi Islam-Kristen di Maluku melalui lensa teologi sakramental Susan Ross. Di Maluku, kelompok Islam dan Kristen saling menyerang sebagai akibat dari adanya konflik 1999. Baik Perjamuan Kudus maupun pela menawarkan keunikan proses rekonsiliasi. Dengan menelisik cara berpikir sakramental Susan Ross, pela dan Perjamuan Kudus dapat dikembangkan menjadi ritus baru dapat merangkul komunitas Kristen dan Islam dalam menjaga stabilitas rekonsiliasi tanpa mengurangi perspektif teologi bagaimana Allah bekerja dalam komunitas Maluku.